2020
DOI: 10.1177/1847980420965388
|View full text |Cite
|
Sign up to set email alerts
|

Formation of anisotropic gold nanoparticles on indium tin oxide substrates as a plasmonic sensing material

Abstract: A simple technique of seed-mediated growth has been successfully performed to grow anisotropy gold nanoparticles on solid substrates. The growth of the gold nanoparticles has been carried out in the presence of a binary surfactant mixture of hexadecyltrimethylammonium bromide with two different molecular weights of a capping agent, namely polyvinylpyrrolidone: 40,000 and 55,000. In this study, the effect of process parameters, growth time and molecular weight of capping agent was investigated. The growth time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The changes occurred is depending on the refractive index, n. The n for water is 1.333 and 10 mg/L boric acid is 1.3339 with difference is 0.0009. Hence, the wavelength is redshifted when the medium change from DI water to boric acid as well as the intensity increase for higher n. The changes for these sensing responses can be described using Mie theory [27,28,43]. Besides, the PL5-2 with higher density of Au nanoplates has good responses towards different medium as compared to PL5-1.…”
Section: Au Nanoplates Thin Film As a Sensing Materials For Boric Acid Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The changes occurred is depending on the refractive index, n. The n for water is 1.333 and 10 mg/L boric acid is 1.3339 with difference is 0.0009. Hence, the wavelength is redshifted when the medium change from DI water to boric acid as well as the intensity increase for higher n. The changes for these sensing responses can be described using Mie theory [27,28,43]. Besides, the PL5-2 with higher density of Au nanoplates has good responses towards different medium as compared to PL5-1.…”
Section: Au Nanoplates Thin Film As a Sensing Materials For Boric Acid Detectionmentioning
confidence: 99%
“…Previously, many attempts have been done to produce high yield of nanoplates by investigating the seeding process [ 35 ], growth aging period [ 17 ] and the materials, i.e. surfactants and capping agents used in the synthesis process [ 28 ] and also simplifying the process [ 36 ]. As a result, we found that the implementation of PLL in the synthesizing process successfully promotes high yield of Au nanoplates product especially for hexagon shapes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] However, these methods require exhaustive and time-consuming sample preparation and the use of expensive equipment. One of the most promising alternatives is surface enhanced Raman spectroscopy (SERS), 10 because it exhibits rapid response and high sensitivity for the detection of diverse compounds, [11][12][13][14][15] and is an up-and-coming technology that significantly impacts the science and technology of materials, biology, medicine, and environmental monitoring. One of the main challenges for SERS is the design and optimization of suitable substrates that have good features, such as excellent reproducibility, good uniformity, portability, and a high enhancement factor (EF).…”
Section: Introductionmentioning
confidence: 99%